Chlorogenic acids and the acyl-quinic acids: discovery, biosynthesis, bioavailability and bioactivity. Issue 12 (21st November 2017) - Clifford, Michael N.; Jaganath, Indu B.; Ludwig, Iziar A.; Crozier, Alan
Abstract : This review is focussed upon the acyl-quinic acids, the most studied group within the ca. 400 chlorogenic acids so far reported. Abstract : Covering: 2000 up to late 2017 This review is focussed upon the acyl-quinic acids, the most studied group within the ca. 400 chlorogenic acids so far reported. The acyl-quinic acids, the first of which was characterised in 1846, are a diverse group of plant-derived compounds produced principally through esterification of an hydroxycinnamic acid and 1l -(−)-quinic acid. Topics addressed in this review include the confusing nomenclature, quantification and characterisation by NMR and MS, biosynthesis and role in planta, and the occurrence of acyl-quinic acids in coffee, their transformation during roasting and delivery to the beverage. Coffee is the major human dietary source world-wide of acyl-quinic acids and consideration is given to their absorption and metabolism in the upper gastrointestinal tract, and the colon where the microbiota play a key role in the formation of catabolites. Evidence on the potential of the in vivo metabolites and catabolites of acyl-quinic acids to promote the consumer's health is evaluated.